Unix concepts and applications - Das Sumitabha (New Delhi Tata McGraw-Hill, 2001)
This book is divided into two parts, part I covering the fundamental aspects and part II would serve as a ready reference. It covers subsequent Unix flavours i.e SCO UNIX Open Server Release 5, SCO UNIXware 7, Red Hat LINUX 5.0, SuSe LINUX 5.1
Keywords: Computer operating systems; Unix(Operating system)